Photoconversion of 2-Propanol on Rutile Titania: A Combined Liquid-Phase and Surface Science Study - Kraeuter, Jessica; Mohrhusen, Lars; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg; Al-Shamery, Katharina (Journal of Physical Chemistry C, 2021)
A fundamental reaction in industries for producing aldehydes and ketones is the partial oxidation of alcohols. As a model reaction, we investigated the photo-oxidation of 2-propanol on rutile titania, which is a promising chemically nontoxic photocatalyst. Photochemical infrared reflection absorption spectroscopy (PC-IRRAS) was used to study the reaction on powder catalysts in the liquid phase (neat liquid and dissolved in dichloromethane). We compare these results with polarized Fourier transform (FT)-IRRAS and temperature-programmed desorption (TPD) experiments on rutile TiO2(110) single crystals in ultrahigh vacuum (UHV). Our in situ liquid-phase experiments showed that 2-propanol converts into acetone on rutile powders, which is in accordance with previous ex situ studies. Mass transport limitations are the key to avoid total oxidation. However, the yield of acetone is limited. We identified water formed as a byproduct and suspected that water might block the active sites. To elucidate possible reaction mechanisms, further experiments were performed on rutile TiO2(110) single crystals in the presence and absence of oxygen and UV irradiation under UHV conditions. Here, we obtained further insights into the elementary steps of the different 2-propanol reactions. We demonstrated that acetone desorbs from a diolate species, which forms in the presence of oxygen under UV irradiation at temperatures around 200 K. Furthermore, propane was identified for the first time as a new thermally activated deoxygenation product besides the simultaneously formed, formally reported, propene. Propene formation is quenched by UV irradiation. Active site blocking by water is confirmed by TPD and polarized FT-IRRAS measurements.
CRIS-Team Scopus Importer:2021-03-19